Stress and distortion analysis of a swept box beam having bulkheads perpendicular to the spars - Heldenfels, Richard R. (National Advisory Committee for Aeronautics, 1950)
A method is presented for the approximate calculation of the stresses and distortions in a box beam representing the main structural component of a swept wing with a carry-through section and with bulkheads perpendicular to the spars. The application of the method is illustrated by a numerical example and its results are compared with previously published test data.
Date of issue: November 1950.
Report no. NACA-TN-2232